Relationship Between Body Mass Index and Anemia in Pregnancy and the Incidence of Primary Postpartum Hemorrhage at RSUD Blambangan Banyuwangi - Yusriyyah, Izdihaar; Sri Rejeki, Purwo; Andriyanti, Andriyanti (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Primary PPH is a leading cause of maternal mortality, and maternal factors such as anemia and nutritional status measured by Body Mass Index (BMI) may influence its occurrence. However, existing evidence on the association between these factors and primary PPH remains inconsistent. Objective: This study aimed to analyze the relationship between BMI and anemia during pregnancy and the incidence of primary postpartum hemorrhage at RSUD Blambangan Banyuwangi. Methods: A retrospective case–control design was used involving 120 postpartum women, comprising 60 cases of primary PPH and 60 controls without PPH. Total sampling was applied using medical records from January to December 2024. Data analysis employed the Chi-Square test, and risk estimates were calculated using Odds Ratios (OR). Results and Discussion: The major causes of primary PPH included uterine atony (43.34%), cervical rupture (28.33%), retained placenta (20%), and perineal rupture (8.33%). Anemia showed a significant association with primary PPH (p = 0.001; OR = 3.455), indicating that anemic pregnant women had a 3.4-fold increased risk of experiencing PPH. Conversely, BMI did not demonstrate a significant relationship with PPH, suggesting that nutritional status may play a lesser role compared to hematological factors. Conclusions: Anemia during pregnancy is significantly associated with primary PPH, whereas BMI shows no significant association. Enhanced antenatal screening and effective management of anemia are essential for reducing the risk of PPH.